Mathematical models for drug delivery from textile. (March 2021) - Martí, Meritxell; Martínez, Vanessa; Lis, Manel J; Coderch, Luisa
Gallic acid was microencapsulated in poly-ɛ-caprolactone by the solvent evaporation method and was applied onto biofunctional textile substrates, cotton, and polyamide fabrics using a finishing process. A higher content of microspheres on polyamide was obtained due to the more hydrophobic character of polyamide. Drug release in physiological serum was carried out with treated fabrics submerged into a thermostatized vessel at semi-infinite bath conditions. The kinetic study carried out allowed the determination of the drug-delivery behavior for all systems in the medium. The results showed that the hydrophobicity and affinity of textiles and gallic acid influenced the release mechanism. For cotton, a clear Fickian diffusion was obtained; for polyamide, the diffusion was anomalous. However, no differences were found in the global mass transport. The model could address the need of the medical and health sector for assessing the theoretical amount of drug released from biofunctional textile.